Single-Substrate High-T/sub c/ Superconducting Coplanar Oscillator at 6.5 GHz - Klieber, Ralf; Ramisch, Roland; Weigel, Robert; Schwab, Martin; Valenzuela, Alejandro; Dill, Roland; Russer, Peter (Asia-Pacific Microwave Conference (APMC), 1992, 1992)
The design and performance of a planar, low-noise cryogenic oscillator operating at 6.5 GHz and 77 K are presented. The device is entirely fabricated on a 10x10 mm² LaAlO₃ substrate with a superconducting YBa₂Cu₃O₇₋x thin-film as the conductor material. At a power output of 4.9 dBm, we attain a single-sideband phase noise to carrier ratio of -90 dBc/Hs at 10KHz offset. The attenuation of harmonics was better that 10 dBc.
elib2cris::1512001600,klieber1992a
Keywords: Coplanar waveguides; Cryogenics; Frequency; High temperature superconductors; Oscillators; Substrates; Superconducting materials; Superconducting microwave devices; Superconducting thin films; Thin film circuits